Calculation of geometric parameters of a magnetic quadrupole lens working near to saturation - Mytsykov, A.O. (Вопросы атомной науки и техники, 2000)
The method for defining basic geometric parameters of precision quadrupole lenses is offered. The method allows one to obtain the field of working area differing from required one less than by 10⁻⁴ compared with the basic component. The lens shape is described by 2 parameters. The method allows taking into account the field distortions caused by saturation of iron. Moreover, it is possible to calculate lenses with a complicated multipolar structure including the forbidden field harmonics. The paper contains the results of calculations for lense shapes used in actual installations.